Analysis of Syed Nawab Haider Naqvi's Islamic Ethics System on Leveling Option of Expeditionary Services on Shopee Marketplace - Lestari, Yosy Arik Putri; Damanuri, Aji (Fakultas Syariah INSURI Ponorogo, 2022)
This study aims to analyze the sharia ethical system of the buyer's rights in choosing shipping services in the Shopee marketplace and the sharia moral system to changes in the pricing of shipping services in the Shopee marketplace. This research is field research using a qualitative approach, with data collection techniques through interviews and documentation. Then data analysis is done by data reduction, presentation, and conclusion. The results show that the leveling option policy on the aspect of the right to vote for the delivery service buyer does not reflect the overall value of justice. After all, there is the right to choose the price and the right to select the delivery service quality that is not by the axioms of monotheism, balance, free will, and responsibility, but the right to choose estimates. Time has implemented these four axioms because they were by their designation at the beginning of the program and supported by changes in the features of the expedition service. The shift in pricing with a one-price system has not provided complete justice according to the four hypotheses because the existence of a one-price system triggers a gap between buyers who are geographically far from the city and shipping costs that exceed the limit. The value of the free shipping voucher was greatly affected by the failure. Get the best price, while buyers who are in geographical conditions near the city with shipping costs that do not exceed the value of the free shipping voucher are not affected because the free shipping voucher helps get the best price.